PENGEMBANGAN VIDEO PEMBELAJARAN INTERAKTIF BERBASIS WONDERSHARE FILMORA PADA MATERI SENI LUKIS UNTUK SISWA SMP - Krisna Bayu Saputra; Sholeh Hidayat; Lukman Nulhakim (Akademika, 2023)
This study aims to produce a product in the form of an interactive learning video based on the Wondershare Filmora application in art and culture subjects in painting material to increase learning effectiveness and make it easier for students to absorb the material. Researchers use the Research and Development (R&D) method with the Borg and Gall model as a guide for developing an effective product. The research procedure is to analyze the needs of students, design the required teaching materials, develop teaching materials that have been designed, implement them on students and evaluate the results of implementing teaching materials. The results of the development show that interactive learning videos based on the Wondershare Filmora application can increase student motivation because they provide an attractive appearance with content inserted in the form of video tutorials and are accompanied by solid and clear backsounds and narratives to support the interactive learning media being developed and can help students understand real form of the material being studied. Increasing educators' knowledge regarding the development of teaching materials, increasing learning effectiveness and growing motivation and interest in learning students are the results obtained. However, on this occasion the researcher only focused on developing teaching materials.